2nd International Conference on Mechanical, Manufacturing and Process Plant Engineering - Awang, Mokhtar (Springer, 2017)
This volume presents selected papers from the 2nd International Conference on Mechanical, Manufacturing and Process Plant Engineering (ICMMPE 2016) which was held from 23rd to 24th November, 2016 in Kuala Lumpur, Malaysia. The proceedings discuss genuine problems of joining technologies that are heart of manufacturing sectors. It discusses the findings of experimental and numerical works from soldering, arc welding to solid state joining technology that faced by current industry.
Keywords: Production engineering -- Congresses.; Mechanical engineering -- Congresses.; Friction stir welding -- Congresses.; elektronické knihy; electronic books